ChiroVox : A public library of bat calls - Görföl, Tamás; Huang, Joe Chun-Chia; Csorba, Gábor; Gyorössy, Dorottya; Estók, Péter; Kingston, Tigga; Szabadi, Kriszta Lilla; McArthur, Ellen; Juliana, Senawi; Furey, Neil M.; Tully, Vuong Tan; Thong, Vu Dinh; et al. (PeerJ Inc., 2022)
Recordings of bat echolocation and social calls are used for many research purposes from ecological studies to taxonomy. Effective use of these relies on identification of species from the recordings, but comparative recordings or detailed call descriptions to support identification are often lacking for areas with high biodiversity. The ChiroVox website (www.chirovox.org) was created to facilitate the sharing of bat sound recordings together with their metadata, including biodiversity data and recording circumstances. To date, more than 30 researchers have contributed over 3,900 recordings of nearly 200 species, making ChiroVox the largest open-access bat call library currently available. Each recording has a unique identifier that can be cited in publications; hence the acoustic analyses are repeatable. Most of the recordings available through the website are from bats whose species identities are confirmed, so they can be used to determine species in recordings where the bats were not captured or could not be identified. We hope that with the help of the bat researcher community, the website will grow rapidly and will serve as a solid source for bat acoustic research and monitoring.